The effectiveness of topical colloidal silver in recalcitrant chronic rhinosinusitis: a randomized crossover control trial. Issue 1 (December 2017) - Scott, John; Krishnan, Rohin; Rotenberg, Brian; Sowerby, Leigh
Abstract Background Recalcitrant chronic rhinosinusitis without polyposis (CRSsP) is a challenging condition to manage as traditional medical therapies and surgery fail to provide satisfactory clinical improvements. Colloidal silver (CS), a widely used naturopathic agent, has recently shown anti-biofilm properties both in vitro and within a rhinosinusitis animal model. To date, no trials involving humans have been published in world literature. The purpose of this study was to assess the efficacy of CS as a topical nasal spray in patients with refractory CRSsP. Methods A prospective cohort study was conducted using a convenience sample of 20 randomized patients with crossover methodology, comparing nasal sprays with CS versus saline. Patients sprayed twice daily for six weeks with the first intervention and then switched to the second for the next six weeks, with measurements made at baseline and each time point. Primary outcomes were changes in SNOT-22 and Lund-Kennedy (LK) endoscopic scores. All analysis was non-parametric and was conducted using STATA 14. Results Twenty-two patients were enrolled in the study with 20 completing the entire protocol. Mean 6-week change in SNOT-22 scores were −2.8 and 1.0 for saline and CS, respectively (p = 0.373). Similarly, mean 6-week change in LK scores were −1.4 and −1.1 for saline and CS, respectively (p = 0.794). Significant period effects were observed with the SNOT-22 score between the randomized groups. No participants experienced negative health effects directly attributable to the administration of intranasal CS. Conclusion Commercially available CS nasal spray did not demonstrate any meaningful subjective or objective improvements in patients with recalcitrant CRSsP. Trial registration NCT02403479 . Registered on March 1, 2015.